Distribution and abundance of marine wood borers on the west coast of Peninsular Malaysia - Singh, H.R.; Sasekumar, A. (Kluwer (now part of Springer), 1994)
Twenty one species of marine wood borers were recorded in this study. There are seventeen species of bivalves of which sixteen are from the family Teredinidae and one from the family Pholadidae. The crustaceans comprised the family Sphaeromatidae with three species and the family Limnoriidae with one species. Seven of the fourteen known genera of the teredinids were recorded. The bivalve wood borers were widely distributed in the local mangroves. Martesia striata was the most abundant wood borer at the Degaussing Range jetty, Lumut. Lyrodus pedicellatus was the most abundant shipworm in wooden panels. Shipworms were abundant on the subtidal panels where the genus Bankia, was most common while M. striata was abundant on the intertidal panels. M. striata numbers were higher on the top surfaces as compared to the under surfaces of wooden panels.